SheWorks : Putting Gender-Smart Commitments into Practice - International Finance Corporation (Washington, DC, 2017)
Gender gaps in employment, however, are not just an emerging or developing economy problem. Developed economies also have a range of gender gaps to tackle. This report is the culmination of the International Finance Corporation (IFC) - led SheWorks global private sector partnership launched at the 2014 Clinton global initiative annual meeting. The partnership’s aim was to advance employment opportunities and improve working conditions for more than 300,000 women by 2016. The full report consolidates the 13 members’ learning and best practice around the recruitment, retention, and promotion of female employees. SheWorks members and strategic partners have contributed their knowledge and expertise to this report. The aim of this report is to help companies across regions and sectors identify and implement gender-smart recruitment, retention, and promotion policies that work best for their (female) employees and the business. The report concludes with suggestions for future research and partnerships, and highlights issues that were beyond the terms of reference of the SheWorks partnership but vital to advancing women’s employment. The summary provides a brief synopsis of each chapter while additional promising practices and lessons learned are provided in the full report.